Peran Ekstrakurikuler Palang Merah Remaja dalam Membentuk Perilaku Tolong Menolong Peserta Didik - Jannah, Siti Sri Fattul; Nursalim, Eko (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2023)
This research aims to understand the role of the Youth Red Cross (PMR) extracurricular in shaping helping behaviour among teenagers. This research method uses qualitative research methods through a descriptive approach. Researchers collected relevant data through various data collection techniques, such as observation, documentation, and interviews related to the PMR extracurricular program at SMP Negeri 4 Bengalon. The results of this study indicate that PMR extracurriculars have a significant role in shaping helping behaviour among teenagers. PMR programs provide basic knowledge and skills using humanitarian principles so that students are able to understand the importance of helping others and feel inspired to take action to help. Regarding the obstacles faced by the Youth Red Cross (PMR) extracurricular, there needs to be cooperation between the school, parents, and students to support the Youth Red Cross extracurricular.